Cardiovascular responses to high‐intensity stair climbing in individuals with coronary artery disease. Issue 10 (19th May 2022) - Valentino, Sydney E.; Dunford, Emily C.; Dubberley, Jonathan; Lonn, Eva M.; Gibala, Martin J.; Phillips, Stuart M.; MacDonald, Maureen J.
Abstract: Exercise‐based cardiac rehabilitation leads to improvements in cardiovascular function in individuals with coronary artery disease. The cardiac effects of coronary artery disease (CAD) can be quantified using clinical echocardiographic measures, such as ejection fraction (EF). Measures of cardiovascular function typically only used in research settings can provide additional information and maybe more sensitive indices to assess changes after exercise‐based cardiac rehabilitation. These additional measures include endothelial function (measured by flow‐mediated dilation), left ventricular twist, myocardial performance index, and global longitudinal strain. To investigate the cardiovascular response to 12 week of either traditional moderate‐intensity (TRAD) or stair climbing‐based high‐intensity interval (STAIR) exercise‐based cardiac rehabilitation using both clinical and additional measures of cardiovascular function in individuals with CAD. Measurements were made at baseline (BL) and after supervised (4wk) and unsupervised (12 week) of training. This study was registered as a clinical trial at clinicaltrials.gov (NCT03235674). Participants were randomized into either TRAD ( n = 9, 8M/1F) and STAIR ( n = 9, 8M/1F). There was a training‐associated increase in one component of left ventricular twist: Cardiac apical rotation (TRAD: BL: 5.6 ± 3.3º, 4 week: 8.0 ± 3.9º, 12 week: 6.2 ± 5.1º and STAIR: BL: 5.1 ± 3.6º, 4 week: 7.4 ± 3.9º, 12 week: 7.8 ± 2.8º, p (time) = 0.03, η 2 = 0.20; main effect) and post‐hoc analysis revealed a difference between BL and 4 week ( p = 0.02). There were no changes in any other clinical or additional measures of cardiovascular function. The small increase in cardiac apical rotation observed after 4 weeks of training may indicate an early change in cardiac function. A larger overall training stimulus may be needed to elicit other cardiovascular function changes. Abstract : No changes in endothelial function or clinical cardiac function measures after either traditional or stair climbing‐based high‐intensity interval training. After 4 weeks of exercise training, we observed an increase in cardiac apical rotation in individuals with coronary artery disease, which may indicate an early change in cardiac function. Other cardiovascular structural and functional adaptations may be dependent upon both duration of training and baseline fitness status.